A Base‐Resistant ZnII‐Based Metal–Organic Framework: Synthesis, Structure, Postsynthetic Modification, and Gas Adsorption. Issue 8 (15th June 2016) - He, Tao; Zhang, Yong‐Zheng; Wang, Bin; Lv, Xiu‐Liang; Xie, Lin‐Hua; Li, Jian‐Rong
Abstract: A Zn II ‐based metal–organic framework (MOF), [Zn2 (bdp‐CHO)2 ]⋅ (DMF)(CH3 CN)(H2 O)2 (BUT‐31) is reported that was synthesized by the reaction between a newly designed aldehyde‐tagged polypyrazole ligand 2, 5‐di(1 H ‐pyrazol‐4‐yl)benzaldehyde (H2 bdp‐CHO) and a zinc salt. BUT‐31 has a unique pillared layered framework structure with 3D intersecting channels approximately 3.4–5.4 Å in size. Powder X‐ray diffraction and N2 adsorption experiments revealed that BUT‐31 is rigid and permanently porous with the Brunauer–Emmett–Teller surface area of 926 m 2  g −1 . Notably, this MOF tolerates boiling water and even highly basic aqueous solution (4 m sodium hydroxide), although dilute acid gradually decomposes its framework. Owing the permanent porosity and chemical stability of BUT‐31, covalent post‐modification of the free aldehyde group exposed on the pore surface was accomplished by treating the MOF in a concentrated ammonia solution (25 %) at near room temperature, giving rise to an imine‐functionalized analogue of BUT‐31. Gas adsorption results show that the aldehyde‐ and imine‐functionalized MOFs have high CO2 adsorption capacities, as well as CO2 /N2 and CO2 /CH4 adsorption selectivities. Abstract : If you can stand the heat : A Zn II ‐based metal–organic framework (MOF), [Zn2 (bdp‐CHO)2 ]⋅ (DMF)(CH3 CN)(H2 O)2 (BUT‐31) was synthesized through the reaction between an aldehyde‐tagged polypyrazole ligand 2, 5‐di(1 H ‐pyrazol‐4‐yl)benzaldehyde (H2 bdp‐CHO) and a zinc salt. BUT‐31 has a unique pillared layered framework structure with 3D intersecting channels of around 3.4–5.4 Å (see figure). Notably, this MOF tolerates boiling water and even 4 m NaOH, although dilute acid gradually decomposes its framework.